2019
DOI: 10.1096/fasebj.2019.33.1_supplement.lb13
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reduces Proportions of Tumor Resident Myeloid‐Derived Suppressor Cells

Abstract: Myeloid‐derived suppressor cells (MDSCs) are a population of immature myeloid immune cells that promote tumor progression and metastasis by suppressing both innate and adaptive immune responses. Exercise modulates immune function and is generally thought to protect against tumor growth and metastasis, yet the mechanisms behind this protection are largely unknown.PURPOSETo examine how exercise impacts circulating and tissue resident lymphocyte and MDSC populations.METHODSFemale mice were randomly assigned to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies using animal models to mimic human disease can detail the onset, promotion, or progression of disease and identify the potential biological pathways ( Hoffman-Goetz, 2003 ; Ashcraft et al, 2016 ), yet the current results of animal studies in exercise on tumor or the intensity of exercise effect were heterogeneous. Some studies found exercises were effective to slow tumor growth ( Shalamzari et al, 2014 ; Alizadeh et al, 2018 ) and decrease tumor cell number of breast cancer ( Alvarado et al, 2017 ), while other studies reported exercises did not inhibit tumor initiation ( Steiner et al, 2013 ) or have no effect on the tumor volume ( Garritson et al, 2019 ). The reason may be related with the different cancer phenotypes, the different model established methods of mammary adenoma and different exercise schemes (type, duration, intensity, and frequency of exercise).…”
Section: Introductionmentioning
confidence: 99%